A case of chromoblastomycosis by Fonsecaea nubica indicating a possible insect route of transmission. Issue 10 (22nd June 2016) - Chen, Yingdan; Yin, Songchao; Li, Meirong; Chen, Rongzhang; Wei, Ling; Ma, Han; Deng, Shuwen; de Hoog, Gert Sybren; Lai, Wei; Lu, Chun; Feng, Peiying
Summary: A first auricular case of chromoblastomycosis due to Fonsecaea nubica is reported in a 42‐year‐old Chinese male. He presented a slightly verrucous, erythematous plaque on his right auricle which had gradually extended over a 10‐year period, and the patient reported a history of dog flea sting before onset of the lesions. Diagnosis was based on histopathological and mycological examination of clinical samples, which revealed muriform cells. Identification of the aetiological agent was assessed by morphological characteristics and confirmed at species level by sequencing of the rDNA internal transcribed spacer (ITS). The patient showed marked clinical improvement after 3 months combination therapy with itraconazole and terbinafine. The possible mode of transmission of auricular chromoblastomycosis is discussed.